THE INFLUENCE OF ROLE CONFLICT AND LOCUS OF CONTROL ON EMPLOYEE TURNOVER - Taryana Taryana; Granit Agustina; Mochammad Isa Anshori; Rieneke Ryke Kalalo; Joni Kutu’ Kampilong (CV. Adiba Aisha Amira, 2025)
Researchers believe that by involving an employee in a conflict within a company, more employees will turn over or leave the company (Sugiyono, 2019). Apart from that, employee self-control is also key so that employees choose to stay or leave/turn over from a company. Therefore, this research aims to analyze the influence of Role Conflict and Locus of Control on Employee Turnover (Jonathan Sarwono, 2016). This research is quantitative research with an explanatory approach. The data used in this research is primary data that researchers distributed online to PT employees. KAI is spread throughout Indonesia, totaling 300 respondents with a minimum criteria of working for one year (Abdurahman, 2016). This data can also be called primary data. The data that was collected was analyzed using the smart PLS 4.0. The research results show that the Role Conflict variable has a positive relationship and a significant influence on the Employee Turnover variable. This is indicated by the statistical results in table 3. The Path Coefficient shows that the T-Statistics results have a positive direction and are above the standard deviation of 1,960, namely 3,019. Apart from that, the P-Values value which indicates whether it is significant or not is below the 0.05 significance level, namely 0.002. This is because the more employees are involved in a conflict in the company, it makes employees uncomfortable and in the end they can choose another company that can make them more comfortable at work.. This means that the more employees involved in conflict in a company, the more employees will leave a company. Apart from that, the Locus of Control variable also has a significant influence but has a negative relationship on Employee Turnover. This is because the T-Statistics value has a negative relationship that is above the standard deviation of 1,960, namely -2,890. The P-Valus value in this study is also below the significance level of 0.05, namely 0.009. This means that the more employees can control themselves within (Locus/Company), the more employees can do their work well and feel comfortable even though there are many conflicts and problems within a company. So the better the locus of control, the fewer employees will turnover from the company.